FTIR-assisted evaluation of xanthan gum as a biostimulant for groundnut seed priming and growth promotion - Monisha, G; Vijayalakshmi, V; Sathish, S; Manonmani, V; Nakkeeran, S; Gayathry, G (Plant Science Today, 2025)
Experiments were conducted to evaluate the effect of biostimulant-based seed priming on the germination and seedling vigour of groundnut (Arachis hypogaea) seeds. Seeds with 75 % initial germination and 9 % moisture content were primed using xanthan gum, carrageenan, gellan gum, chitosan and gelatin at five concentrations (0.1 %-0.5 %), two soaking volumes (equal and double volume) and three soaking durations (1-3 hr). Seed quality parameters were assessed under both normal and stress conditions. The results indicated that seeds primed with 0.2 % xanthan gum (double volume, 1 hr) showed the highest germination (100 %), root length (16.20 cm), shoot length (8.00 cm) and vigour index (2420). These results were statistically similar to the 0.3 % xanthan gum treatment (double volume, 2 hours). The next best performance was observed with 0.3 % gellan gum (double volume, 1 hr), resulting in 100 % germination, 15 cm root length, 8.30 cm shoot length and a vigour index of 2335. In contrast, untreated control seeds displayed lower performance. The top five priming treatments were further evaluated under water stress conditions (60 %, 70 %, 80 % and 100 % water-holding capacity of sand). Seeds primed with 0.2 % xanthan gum (double volume, 1 hour) achieved the highest germination rates under all stress levels (60 %-100 %), whereas control seeds recorded lowest values. FTIR analysis of xanthan and gellan gum identified key functional groups associated with improved nutrient uptake, stress resistance and enhanced metabolic processes-factors contributing to increased plant growth in primed seeds. Biostimulant seed priming, particularly with xanthan and gellan gum, significantly enhances seed germination, vigour and stress tolerance in groundnut, suggesting a promising pre-sowing treatment for improved productivity in both irrigated and rainfed conditions.